2015
DOI: 10.4103/0974-777x.150887
|View full text |Cite
|
Sign up to set email alerts
|

Risk correlates of diarrhea in children under 5 years of age in slums of Bankura, West Bengal

Abstract: Background:Diarrheal diseases are an important cause of mortality and morbidity globally in children under 5 years of age.Objective:To find the prevalence and risk factors of diarrhea among children under 5 years.Materials and Methods:A population-based analytical cross-sectional study was conducted in the urban slums of Bankura, West Bengal on the prevalence of diarrhea and feeding practices, nutrition, and immunization among 152 children under 5 years (69 males and 83 females).Results:Overall prevalence of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…A 9% diarrhea incidence differential between female and males was found in the year 2014. Bui in 2006 also conducted a research on the most common causes and risk factors for diarrhea among children less than five years of age admitted to Dong Anh Hospital, Hanoi, Northern Vietnam which found females with high incidence for diarrhea, and also Gupta et al [ 33 ] on risk correlates of diarrhea in children under 5 years of age in slums of Bankura, West Bengal, identified females to be more affected with diarrhea (22.89%) than males (21.73%) whereas in the South Indian study females had higher acute diarrhea (23.8%) than males (21.4%) but it was further reported that the difference was not statistically significant [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 9% diarrhea incidence differential between female and males was found in the year 2014. Bui in 2006 also conducted a research on the most common causes and risk factors for diarrhea among children less than five years of age admitted to Dong Anh Hospital, Hanoi, Northern Vietnam which found females with high incidence for diarrhea, and also Gupta et al [ 33 ] on risk correlates of diarrhea in children under 5 years of age in slums of Bankura, West Bengal, identified females to be more affected with diarrhea (22.89%) than males (21.73%) whereas in the South Indian study females had higher acute diarrhea (23.8%) than males (21.4%) but it was further reported that the difference was not statistically significant [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hand washing practices were unsatisfactory and clean drinking water was not available in majority of houses. Study by Gupta et alfound incidence of diarrhea higher in bottle fed children [10]. Study conducted by Durairajet al concluded that unsafe drinking water was significant risk factors for the incidence of diarrhea [8].…”
Section: Original Research Articlementioning
confidence: 98%
“…Tiruvallur district of Tamil Nadu in 2012 by Samyaet al had 51.1% males and 48.9% females [9]. However, study conducted by Gupta et alin slums of Bankura, West Bengal in 2015 had slightly higher prevalence of diarrhea in females (22.89%) than males (21.73%) [10].…”
Section: Study Conducted In 370 Under Five Children In Nemammentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in the urban slums of Bankura, West Bengal, the authors found that poor feeding practices, low immunization rates and poor nutrition statuses increase the risk of diarrhoea among the under five children and health education helped in tackling these risk factors. 12 In a systematic review, Das et al also found that community based interventions on health education and treatment have reduced diarrhoea related morbidity and mortality and have potential for scale-up. 13 Based on our findings and supportive evidence from different parts of the world, we conclude that our community based interventions in urban and rural settings have contributed to the reduction in diarrhoea incidence and longitudinal prevalence primarily by modifying the risk factors.…”
Section: Journal Of Global Health Reportsmentioning
confidence: 99%